Muscle‐specific Cand2 is translationally upregulated by mTORC1 and promotes adverse cardiac remodeling. (4th October 2021) - Górska, Agnieszka A; Sandmann, Clara; Riechert, Eva; Hofmann, Christoph; Malovrh, Ellen; Varma, Eshita; Kmietczyk, Vivien; Ölschläger, Julie; Jürgensen, Lonny; Kamuf‐Schenk, Verena; Stroh, Claudia; Furkel, Jennifer; et al.
Abstract: The mechanistic target of rapamycin (mTOR) promotes pathological remodeling in the heart by activating ribosomal biogenesis and mRNA translation. Inhibition of mTOR in cardiomyocytes is protective; however, a detailed role of mTOR in translational regulation of specific mRNA networks in the diseased heart is unknown. We performed cardiomyocyte genome‐wide sequencing to define mTOR‐dependent gene expression control at the level of mRNA translation. We identify the muscle‐specific protein Cullin‐associated NEDD8‐dissociated protein 2 (Cand2) as a translationally upregulated gene, dependent on the activity of mTOR. Deletion of Cand2 protects the myocardium against pathological remodeling. Mechanistically, we show that Cand2 links mTOR signaling to pathological cell growth by increasing Grk5 protein expression. Our data suggest that cell‐type‐specific targeting of mTOR might have therapeutic value against pathological cardiac remodeling. SYNOPSIS: Genome‐wide translational profiling identifies mTORC1‐dependent genes in cardiomyocytes in response to neurohumoral stimulation. Expression of the muscle‐specific gene Cand2 is controlled by mTORC1 and Cand2 regulates cardiac function and pathological hypertrophy. Cand2 is translationally upregulated during pathological stress in cardiac myocytes. Cand2 expression depends on the activity of mTORC1. Cand2 promotes the expression of G‐protein coupled receptor 5 (Grk5), which in turn links to myocyte enhancer factor 2 (MEF2)‐driven transcription of cardiac hypertophy genes. Abstract : Genome‐wide translational profiling identifies mTORC1‐dependent genes in cardiomyocytes in response to neurohumoral stimulation. Expression of the muscle‐specific gene Cand2 is controlled by mTORC1 and Cand2 regulates cardiac function and pathological hypertrophy.